Sustainable Urban Development in Smart Cities: Leveraging IoT for Inclusive Growth - Hasan Abdullah (Global Writing Academica Researching & Publishing, 2024)
The rapid urbanization of the 21st century has necessitated the development of sustainable and inclusive urban environments, particularly in the context of smart cities. This article explores the role of the Internet of Things (IoT) in advancing sustainable urban development by addressing key challenges such as resource optimization, environmental conservation, and equitable access to public services. A systematic review of existing literature highlights innovative IoT applications in areas like waste management, energy efficiency, and transportation. The study employs a comparative analysis of case studies from emerging and developed economies, illustrating diverse approaches to IoT integration. Findings reveal that while IoT technologies significantly enhance urban sustainability and inclusivity, challenges persist in terms of data privacy, infrastructure costs, and governance. The article concludes by proposing a framework for policymakers to balance technological innovation with regulatory safeguards, ensuring smart cities are both resilient and socially inclusive.